Pembangunan Imunitas Sebagai Gaya Hidup Baru dalam Menghadapi Pandemi Covid-19 Lewat Pendampingan Kader PKK di RT.03, RW.02 Tanjungsari Surabaya - Indrawati; Roseta, Charolin Indah; Utami, Ana Widya (Proceedings of Annual Conference on Community Engagement, 2022)
The most effective effort to deal with Covid-19 is preventive rather than curative. With this basis, this PKM is carried out in order to provide prevention efforts through assistance in developing immunity as a new lifestyle in dealing with Covid-19 for PKK RT cadres. 03, RW. 02, Tanjungsari Surabaya. This assistance is carried out through an outreach approach (delivery of insight, dialogue/discussion and question and answer in the form of games) as well as a mentoring approach by means of problem solving for various difficulties in implementing immunity development as a new lifestyle. After the counseling, within a certain period of time, monev is carried out to check the final impact of the results of the mentoring. The final result of the mentoring shows that many residents have difficulty implementing immunity development as a new lifestyle because some of the PKK cadres come from low-income communities. For this reason, it is necessary to carry out further treatment, namely assistance in developing immunity as a new lifestyle in the context of low-income communities.